الأخلاق وعلاقتها بالنهوض الحضاري دراسة تحليلية لكتاب شروط النهضة مالك بن نبي - عنيق نصر, خولة (University of Eloued جامعة الوادي, 2017)
عالجت هذه الدراسة الأخلاق وعلاقتها بالنهوض الحضاري(دراسة تحليلية لكتاب شروط النهضة لمالك بن نبي) وهي تهدف إلى معرفة علاقة الأخلاق بالنهوض الحضاري انطلاقا من التساؤل الرئيسي المتمثل في:" ما مدى ارتباط الأخلاق بالنهوض الحضاري" ؟ وكيف ينظر إليها مالك بن نبي من خلال كتابه شروط النهضة؟,كما اعتمدت الدراسة على المنهج التحليلي ويتخلله المنهج الوصفي,وقسمت الدراسة إلى مقدمة وفصلين الفصل الأول:مدخل عام لدراسة الأخلاق وعلاقتها بالنهوض الحضاري والفصل الثاني:علاقة الأخلاق بالنهوض الحضاري عند مالك بن نبي ــ كتاب شروط النهضة ـ وتوصلت الدراسة إلى مجموعة من النتائج أهمها: • الأخلاق تحتل مكانة مركزية في فكر مالك بن نبي. • الأخلاق منتج من منتجات الحضارة ومكوناتها إذ تشتمل على جانبين مادي ومعنوي الذي تندرج تحته الأخلاق. • الأخلاق عامل من عوامل النهوض الحضاري التي يجب توافرها إذ لا يمكن أن تقوم الحضارات من دونها. This survey has handled the morals and its relationship with civil advancement(analytical analysis in the book of the conditions of Renaissance Malek Ben Nabi s)and it aims to know the relationship between the morals and the civil advancement starting with the main question which onphesis on how much is the link between the morals and the civil advancement ? and how Malek Ben Nabi books to it through his book "the conditions of Renaissance"? this survey deals also on the analytical approach with the descriptive and historical approach, and this survey is divided into introduction and two parts. The first part: A general entrance to study the morals and its relationship with the civil advancement ,the second part: the relationship with the civil advancement of Malek Ben Nabi the Book of "she condition of Renaissance" and deals to treat a group of results like: *The morals tahes a principal position in Malek Bin Nabi s opinion. *The morals are one of the civil productions, it contains two parts Material and moral that the morals fall under it. *The morals are one of the causes of the civil Renaissance which it must exist to reach the renaissance.
مذكرة ماستر تخصص دعوة واعلام
Keywords: الأخلاق النهوض الحضاري، القيم الأخلاقية، مالك بن نبي: ethical promotion of civilization, moral values, malik bin nabi.